Fenomena Jasa Joki Tugas Kuliah di Kalangan Mahasiswa Universitas Udayana - Noviana, Ni Komang Ayu; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
Students as agents of change certainly have adequate academic insight and abilities. However, in practice, many students commit academic fraud in their studies, one of which is by using assignment jockey services. This study was conducted to determine the use of assignment jockey services at Udayana University using a qualitative approach and interview method with the Rational Choice theory proposed by James Samuel Coleman. The study was conducted by interviewing informants, namely students who use assignment jockey services and non-users of assignment jockey services from various faculties at Udayana University, which are divided into exact and non-exact faculty categories. The results reveal that students who knew about assignment jockey services came from promotions on social media, and those who used assignment jockey services came from non-existent faculties. The main reasons students used these services were due to time constraints, lack of understanding of the material, and the desire to get better grades. The use of assignment jockey services certainly provides convenience for students who are constrained in doing assignments, even though it hurts academic development and integrity. Students decided to use assignment jockey services based on decisions that were considered rational through a rational choice process, such as determining priorities, considering available resources, selecting available options, considering success, and exchanging resources. This study expects a stricter academic policy to suppress the practice of using task jockeys in the academic environment so that students can be more responsible for the tasks they have. Keywords: Students, Jockey Services, Phenomenon.